The Implementation of Consignment Sales on Golden Voice Online Store Semarang - Saifudin, Saifudin; Rahmawati, Nurul; Rizkiana, Citra (Universitas Semarang, 2019)
This study was conducted at Golden Voice Online Store Semarang. The purpose of this study is to analyze the implementation of consignment sales and the recording method used in Golden Voice Online Store. This study uses qualitative method of case study by using triangulation of data sources, namely observation, interview and documentation. The sources of the data taken were the data from Golden Voice Online Store. The results of this study indicate that in the financial statements, Golden Voice Online Store has not recorded the consignment in accordance with the applicable Accounting Standard. The method of accounting recording for consignment sales used is inseparabled method.